Leucaena under attack - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Long considered virtually pest-free, leucaena is succumbing to a small bug from Cuba. The psyllid insect, Heteropsylla cubana is a small plant louse resembling a miniature cicada. It spreads both by jumping and by riding in high altitude air...